PENENTUAN JALUR TERBAIK MASUK KOTA SAMPAI KE KAMPUS UNEJ DENGAN METODE ALGORITMA DIJKSTRA - Putra, Arief Rachman Eka; Sukmawati, Sri; Sulistyono, Sonya (FSTPT Indonesia, 2015)
The traveler is always looking for the fastest route to reach the destination point. Similarly, guests of the Jember University come from outside the city, especially from the direction of Surabaya and reverse direction. To find the quickest route to the University of Jember, it takes distance and time information throughout the road leading to the campus of University of Jember. Using Dijkstra's algorithm method, distance and time of data may be processed in order to determine the fastest route to the Campus University of Jember. The results of the survey and analysis shows that the main roads include Jl. HayamWuruk, Jl. Gajah Mada, Jl. Sultan Agung and Jl. PB Sudirman became the fastest route to get to the Campus of the University of Jember.